Answer:
f(g (x))= 32x-18
g (f (x))=32x2+42
Step-by-step explanation:
f (g (x))= 4 (8x-6)+6
32x-24-6
32x-18
g (f (x))= 8(4x2+6)-6
32x2+48-6
32x2+42
Answer:
m = 13.
Step-by-step explanation:
Recall that adding logarithmic equations, (ex: log a + log b) is the same as log (a·b). Therefore:
log 12 + log 5 = log (4m + 8)
log (12·5) = log (4m + 8)
log (60) = log (4m + 8) **Ignore 'Log' to solve for 'm'
60 = 4m + 8 **Subtract both sides by 8
52 = 4m **Divide both sides by 4
m = 13.
Answer:
mee I'm in 8th
Step-by-step explanation:
plzz help will be very thankful
Answer:
31=1/1
33=1/1
30=3/10
3-=-3
Step-by-step explanation:
Answer:
a) No.
b) Yes.
Step-by-step explanation:
a) It's not proportional. Although the graph represents a straight line, it does not pass through the origin (0,0).
b) It is proportional. It is a straight line that passes through the origin.